Translating Bourdieu into youth studies. (2nd January 2020) - Bessant, Judith; Pickard, Sarah; Watts, Rob
ABSTRACT: Against a backdrop of lively discussion about the best ways to do youth studies, or sociology of youth, this article asks: Can Pierre Bourdieu's work be translated into youth studies in ways that benefit the field? We begin by considering Bourdieu's thoughts on the category of 'youth' using a new translation of this text, and then turn to an important discussion by Furlong, Woodman, and Wyn about certain long standing tensions in youth studies. These tensions are between writers engaging in the 'structure versus agency' debate that is mapped onto the 'culture versus transitions' binary. We consider the case for adopting a 'middle-ground' represented by Bourdieu's writings. We argue that many in youth studies work from an unacknowledged substantialist tradition, which is contra to Bourdieu's relational perspective. The result includes misunderstandings of Bourdieu's thinking and expectations of his work, for example, that it can pass certain empirical tests. We argue that if Bourdieu's relational perspective is to be translated into youth studies, we will need a more determined effort to understand that perspective first.